SiC composite substrate
Patent Information
- Application Number
- JP2021031170
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-26
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2041-02-26
Smart Images

Figure 0007636908000002 
Figure 0007636908000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a SiC composite substrate. [Background technology]
[0002] In recent years, semiconductor devices using gallium nitride (GaN) etc. have been put to practical use. GaN crystals can be formed by vapor phase growth methods such as hydride vapor phase epitaxy (HVPE method) and metalorganic chemical vapor deposition (MOCVD method).
[0003] It is known that in such semiconductor devices, the fewer cracks and higher crystallinity in the material, the better the characteristics can be obtained. For example, it is known that the difference in lattice constant and thermal expansion coefficient between the base substrate for film formation and the semiconductor film such as GaN formed on it affects the degree of cracks and crystallinity of the semiconductor film.
[0004] In this regard, various types of base substrates are used for manufacturing GaN crystals, such as sapphire substrates, Si substrates, SiC substrates, substrates with SiC deposited on them, and substrates with a buffer layer on sapphire or Si substrates. Among these, for example, sapphire substrates and Si substrates have a large difference in lattice constant and thermal expansion coefficient with GaN, which causes distortion at the interface between the GaN crystal and the substrate, and the distortion causes cracks in the GaN crystal. SiC single crystal is used as the SiC substrate, and since the difference in lattice constant and thermal expansion coefficient of the SiC single crystal substrate with GaN is relatively small, it can relatively suppress cracks in the GaN crystal, but it is expensive, which increases the manufacturing cost. As for the substrate with SiC deposited on the Si substrate, although the difference in lattice constant of the SiC on the deposition surface with GaN is small, the difference in thermal expansion coefficient between the substrate and GaN is large because the Si substrate is included in the base substrate, and therefore the cracks cannot be sufficiently reduced. Regarding a buffer layer provided on a sapphire or Si substrate, for example, Patent Document 1 (Patent Publication No. 5433909) describes that the degree of warping and cracking is relatively mitigated by stacking several hundred ultra-thin film pairs of AlN (thickness 5 nm) / GaN (thickness 20 nm) on a Si substrate. However, this type of manufacturing method has the problem of complicated processes and high costs.
[0005] Also, for example, Patent Document 2 (Japanese Patent No. 6387375) discloses a semiconductor substrate including a single crystal SiC substrate and a polycrystalline SiC substrate. A part of the single crystal layer into which ions have been implanted is peeled off to obtain a semiconductor substrate including a thin single crystal SiC substrate on a polycrystalline SiC substrate. However, when ions are implanted, the obtained single crystal SiC substrate becomes thin, and it is considered that the polycrystalline SiC affects the GaN crystal film formation, resulting in poor crystallinity of the GaN crystal.
[0006] In addition, for example, Patent Document 3 (JP Patent No. 3254557) discloses single crystal SiC in which a composite of an α-SiC single crystal and an amorphous or β-SiC polycrystalline substrate is bonded to each other and then heat-treated to recrystallize the amorphous or β-SiC polycrystalline substrate, thereby integrally growing a single crystal oriented in the same direction as the crystal axis of the α-SiC single crystal substrate. However, compared to β-SiC, α-SiC has a larger difference in lattice constant with GaN, which is thought to adversely affect the degree of cracking and crystallinity of the semiconductor film. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 5433909 [Patent Document 2] Patent No. 6387375 [Patent Document 3] Patent No. 3254557 Summary of the Invention
[0008] As described above, the difference in lattice constant and the difference in thermal expansion coefficient between the base substrate for film formation and the semiconductor film such as GaN formed thereon affect the degree of cracking and crystallinity of the semiconductor film, so a substrate capable of forming a semiconductor film with high crystallinity and suppressed cracking is desired as the base substrate. It is also desired to reduce the manufacturing cost of the semiconductor film.
[0009] The inventors have now discovered that by fabricating a SiC composite substrate having a single-crystal SiC layer of a predetermined thickness on a polycrystalline SiC layer as a base substrate, and then forming a GaN crystal on the SiC composite substrate, it is possible to obtain GaN crystals that are highly crystalline and have reduced cracks at low cost.
[0010] Therefore, an object of the present invention is to provide a SiC composite substrate that can serve as a base substrate for growing GaN crystals, and that can provide GaN crystals with high crystallinity and reduced cracks at low cost.
[0011] According to one aspect of the present invention, there is provided a SiC composite substrate comprising a polycrystalline SiC layer and a single-crystal SiC layer having a thickness of 1.0 to 30 μm on the polycrystalline SiC layer. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a conceptual diagram showing the configuration of an aerosol deposition (AD) device 50. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] SiC composite substrate The SiC composite substrate according to the present invention comprises a polycrystalline SiC layer and a single-crystal SiC layer having a thickness of 1.0 to 30 μm on the polycrystalline SiC layer. In this way, a SiC composite substrate having a single-crystal SiC layer of a predetermined thickness on a polycrystalline SiC layer is fabricated as a base substrate, and a GaN crystal is formed on the SiC composite substrate, thereby making it possible to obtain GaN crystals with high crystallinity and suppressed cracks at low cost.
[0014] As described above, the difference in lattice constant and the difference in thermal expansion coefficient between the base substrate for film formation and the semiconductor film such as GaN formed thereon affect the degree of cracking and crystallinity of the semiconductor film, so it is desirable to have a base substrate that can obtain a semiconductor film with high crystallinity and suppressed cracking. It is also desirable to reduce the manufacturing cost of the semiconductor film. In this regard, according to the present invention, a SiC composite substrate having a monocrystalline SiC layer of a predetermined thickness on a polycrystalline SiC layer is prepared as a base substrate, and GaN crystals are formed on the SiC composite substrate, thereby making it possible to obtain GaN crystals with high crystallinity and suppressed cracking at low cost.
[0015] The reasons why GaN crystals with high crystallinity and suppressed cracks can be obtained inexpensively are assumed to be as follows. (i) The difference in thermal expansion coefficient between the single crystal SiC layer on which the GaN crystals are formed and the lattice constant is relatively small, and the difference in lattice constant is also small, so that the GaN crystals formed on the SiC composite substrate of the present invention can be made to have high crystallinity and suppressed cracks. (ii) In addition, the SiC composite substrate of the present invention has a polycrystalline SiC layer, but since the crystal orientation of the polycrystalline SiC layer is random, the directions of thermal expansion and thermal contraction are also random. Therefore, the strains that enter the surface of the polycrystalline SiC layer are also random, which affects the single crystal SiC layer, and the crystallinity of the obtained GaN crystal is deteriorated. This effect becomes greater as the single crystal SiC layer becomes thinner. However, the single crystal SiC layer of the SiC composite substrate of the present invention has a thickness of 1.0 to 30 μm and is less susceptible to the above-mentioned effects of the polycrystalline SiC layer, so that GaN crystals with high crystallinity and suppressed cracks can be obtained. (iii) Furthermore, compared to a case where an expensive single crystal SiC substrate itself is used as a base substrate, the SiC composite substrate of the present invention has a single crystal SiC layer on an inexpensive polycrystalline SiC layer, and therefore the manufacturing cost can be reduced. For these reasons, the SiC composite substrate of the present invention can provide a semiconductor film with high crystallinity and suppressed cracks at low cost on the SiC composite substrate. This SiC composite substrate can be used as a base substrate for crystals used as semiconductor films, such as SiC crystals, and is not limited to GaN crystals.
[0016] The thickness of the single crystal SiC layer of the SiC composite substrate of the present invention is 1.0 to 30 μm. This thickness is preferably 2.0 to 30 μm. This makes it possible to effectively obtain GaN crystals with high crystallinity and suppressed cracks. As described above, if the single crystal SiC layer is too thin, the crystallinity of the GaN crystals will deteriorate. The reason is unclear, but the following is considered. Unlike single crystals, the orientation of the particles in a polycrystalline SiC layer is random, so that the directions of thermal expansion and thermal contraction are different for each particle on the polycrystalline surface. Therefore, when the temperature is raised to the film formation temperature of the GaN crystals or when the temperature is lowered after film formation, it is considered that non-uniform distortion in the plane due to the variation in the particle orientation of the polycrystalline part is introduced into the single crystal SiC layer in contact with the polycrystalline SiC layer. If the single crystal SiC layer is thin, the influence of this distortion extends to the film formation surface of the single crystal SiC layer on which the GaN crystals are formed, and as a result, it is considered that the crystallinity of the GaN crystals may deteriorate. For these reasons, the thickness of the single crystal SiC layer is 1.0 μm or more. If the single crystal SiC layer is too thick, it is disadvantageous in terms of manufacturing costs. Therefore, the thickness of the single crystal SiC layer is 30 μm or less.
[0017] Thus, it is considered that the thickness of the single crystal SiC layer affects the manufacturing cost, crystallinity, and degree of cracking of the GaN crystal. Here, for example, Patent Document 2 (Japanese Patent No. 6387375) discloses a semiconductor substrate including a single crystal SiC substrate and a polycrystalline SiC substrate for the purpose of improving electrical characteristics. It describes that a single crystal layer into which ions have been implanted is bonded to a support substrate of polycrystalline SiC, and a part (most part) of the single crystal layer is peeled off at the ion implanted portion to obtain a semiconductor substrate including a thin single crystal SiC substrate on the polycrystalline SiC substrate. However, it is generally difficult to process a position deeper than 1.0 μm by ion implantation. Therefore, it is estimated that the thickness of the single crystal portion of the obtained semiconductor substrate is substantially 1.0 μm or less. That is, it is considered that the crystallinity is deteriorated due to the influence of polycrystalline SiC during the GaN crystal film formation. On the other hand, according to the SiC composite substrate of the present invention, as described above, by forming a GaN crystal film on the SiC composite substrate, it is possible to obtain a GaN crystal with high crystallinity and suppressed cracking at low cost.
[0018] The polytype of the single crystal SiC layer is preferably 3C. That is, the single crystal SiC layer is preferably β-SiC single crystal. By using 3C-SiC, the difference in lattice constant between the single crystal SiC layer and the GaN crystal is small, so that a GaN crystal with high crystallinity and suppressed cracks can be effectively obtained. In particular, the difference in lattice constant between the (111) plane of 3C-SiC and the (002) plane of GaN is small. Here, for example, Patent Document 3 (Japanese Patent No. 3254557) discloses single crystal SiC in which a single crystal oriented in the same direction as the crystal axis of the α-SiC single crystal substrate is integrally grown by heat-treating a composite in which an α-SiC single crystal and an amorphous or β-SiC polycrystalline substrate are closely attached to each other, and the amorphous or β-SiC polycrystalline substrate is recrystallized. For the SiC composite substrate of the present invention, it is preferable to use β-SiC rather than α-SiC, and therefore it is possible to prevent growth in the same direction as the crystal axis of the α-SiC single crystal substrate (not to grow at all). As described above, there are α-SiC and β-SiC in SiC, but the crystal structures of these are completely different, with the former being hexagonal and the latter being cubic, and they can be said to be completely different materials. For example, β-SiC has one type of polymorphism, while more than 200 types of polymorphism have been reported for α-SiC, and it is difficult to obtain a crystal consisting of a single polymorphism. In addition, the stable temperature ranges are different, with β-SiC being stable at relatively low temperatures, while α-SiC is stable at higher temperatures than β-SiC. As described above, α-SiC and β-SiC are completely different materials.
[0019] The polycrystalline SiC layer of the SiC composite substrate of the present invention preferably further contains a rare earth element. It is believed that the polycrystalline SiC layer contains a rare earth element, which more effectively suppresses cracks that may occur in the GaN crystal formed on the SiC composite substrate. Although the reason for this is unclear, it is believed that the presence of an appropriate amount of rare earth elements in the polycrystalline SiC layer relieves distortion in the polycrystalline SiC layer, thereby mitigating warpage of the SiC composite substrate and reducing cracks in the GaN crystal. In addition, it is believed that the rare earth element is preferably contained in the polycrystalline SiC layer by using an oxide of a rare earth element as a raw material. The thermal expansion coefficient of the oxide of a rare earth element is larger than that of SiC, and the thermal expansion coefficient of GaN is larger than that of polycrystalline SiC. Therefore, it is believed that the thermal expansion coefficient of polycrystalline SiC containing an oxide of a rare earth element is closer to that of GaN compared to polycrystalline SiC without the addition of an oxide of a rare earth element. This may reduce the stress caused by the difference in thermal expansion between the SiC composite substrate and the GaN crystal, thereby reducing cracks.
[0020] When the polycrystalline SiC layer contains a rare earth element, the rare earth element is at least one element selected from the group consisting of 17 elements, namely, Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. The inventors have obtained data on the thermal expansion coefficient of oxides of rare earth elements other than Pm and Tb among these rare earth elements, and have confirmed that the thermal expansion coefficient of the oxides of these rare earth elements is greater than that of SiC. The rare earth element contained in the polycrystalline SiC layer is preferably Y (yttrium) and / or Sm (samarium), and more preferably Y.
[0021] When the polycrystalline SiC layer contains a rare earth element, the weight ratio of the content of the rare earth element to the total content of the rare earth element, Si, and C in the polycrystalline SiC layer is preferably 0.00020 to 0.20, more preferably 0.0010 to 0.15, and even more preferably 0.0020 to 0.10. It is considered that by having the weight ratio of the rare earth element within such a range, a GaN crystal with suppressed cracks can be obtained more effectively on the SiC composite substrate. It is considered that by having the weight ratio of 0.20 or less, the influence of distortion caused by the presence of the rare earth element in the polycrystalline SiC layer is prevented from becoming significant, and cracks can be reduced more effectively. In addition, it is considered that the suppression of the generation of a different phase of the rare earth element and SiC, the suppression of the segregation of the rare earth element, and the like also contribute to the reduction of cracks.
[0022] The thickness of the polycrystalline SiC layer of the SiC composite substrate of the present invention is preferably 100 μm or more, more preferably 250 μm or more, from the viewpoint of handling the composite substrate. From the viewpoint of cost, the thickness of the polycrystalline SiC layer is preferably 5000 μm or less, more preferably 3000 μm or less. Therefore, from the viewpoint of achieving both the handleability and cost of the composite substrate, the thickness of the polycrystalline SiC layer is preferably 100 to 5000 μm, more preferably 250 to 3000 μm.
[0023] The SiC composite substrate of the present invention includes a polycrystalline SiC layer and a single-crystalline SiC layer, and the boundary between the single crystal and the polycrystalline can be identified by a known method. For example, it can be identified by obtaining an inverse pole figure orientation mapping of the cross section of the SiC composite substrate using a SEM equipped with an electron backscatter diffraction (EBSD) method. From the obtained inverse pole figure orientation mapping, it is possible to distinguish the oriented layer as the single crystal portion and the other portions as the polycrystalline portion.
[0024] Manufacturing method for SiC composite substrate The method for manufacturing the SiC composite substrate having a polycrystalline SiC layer and a single crystal SiC layer of the present invention is not particularly limited. The polycrystalline SiC layer may be formed directly on the single crystal SiC layer, or the single crystal SiC layer and the polycrystalline SiC layer may be prepared separately and then bonded.
[0025] As the single crystal SiC layer, a commercially available single crystal substrate may be used, or a substrate such as a Si substrate on which SiC is epitaxially grown may be used.
[0026] The polycrystalline SiC layer may be a commercially available polycrystalline substrate, or may be produced by firing a SiC molded body. The SiC molded body may be a tape molded body produced by tape casting, or a green compact produced by pressure molding such as uniaxial pressing. As a firing method, firing may be performed at normal pressure, or pressure firing such as hot pressing or HIP may be performed.
[0027] Examples of the method for forming a polycrystalline SiC layer directly on a single-crystal SiC layer include solid-phase film formation methods such as AD (aerosol deposition) and HPPD (supersonic plasma particle deposition), vapor-phase film formation methods such as sputtering, vapor deposition, sublimation, and various CVD (chemical vapor deposition) methods, and liquid-phase film formation methods such as solution growth. Examples of the CVD method that can be used include thermal CVD, plasma CVD, mist CVD, and MO (metal organic) CVD. Alternatively, a method of placing a SiC molded body on a single-crystal SiC layer may be used.
[0028] When the single crystal SiC layer and the polycrystalline SiC layer are prepared separately and bonded, the bonding method is not particularly limited, but examples include a method using an adhesive, a sintering method, etc. When sintering, the layers may be bonded by applying pressure using a hot press or the like.
[0029] In preparing the polycrystalline SiC layer, the rare earth element can be contained in the polycrystalline SiC layer by making the raw material powder or raw material gas contain a rare earth compound corresponding to the rare earth element. The rare earth compound is not particularly limited, but may be an oxide, nitride, carbide, or fluoride of at least one of the above-mentioned 17 types of rare earth elements. The rare earth compound is preferably an oxide of a rare earth element, and more preferably an oxide of Y (yttrium oxide) or an oxide of Sm (samarium oxide).
[0030] As the manufacturing method of the above-mentioned SiC composite substrate, any of the methods can use known conditions. Below, we will describe a method of directly forming a polycrystalline SiC layer on a single crystal SiC layer by the AD method or thermal CVD method, and a method of placing a previously prepared molded body on a single crystal SiC layer.
[0031] The AD method is a technique in which fine particles or fine particle raw material is mixed with gas to form an aerosol, and the aerosol is sprayed at high speed from a nozzle to collide with a substrate to form a coating, and has the characteristic of being able to form a coating at room temperature. An example of a film forming apparatus (AD apparatus) used in such an AD method is shown in FIG. 1. The AD apparatus 50 shown in FIG. 1 is configured as an apparatus used in the AD method in which raw material powder is sprayed onto a substrate under an atmosphere with a pressure lower than atmospheric pressure. This AD apparatus 50 includes an aerosol generating section 52 that generates an aerosol of raw material powder containing raw material components, and a film forming section 60 that sprays the raw material powder onto a single-crystal SiC layer 20 to form a film containing the raw material components. The aerosol generating section 52 includes an aerosol generating chamber 53 that contains raw material powder and generates an aerosol by receiving a carrier gas from a gas cylinder (not shown), a raw material supply pipe 54 that supplies the generated aerosol to the film forming section 60, and a vibrator 55 that applies vibrations at a frequency of 10 to 100 Hz to the aerosol generating chamber 53 and the aerosol therein. The film formation unit 60 includes a film formation chamber 62 that sprays an aerosol onto the single crystal SiC layer 20, a substrate holder 64 that is disposed inside the film formation chamber 62 and fixes the single crystal SiC layer 20, and an XY stage 63 that moves the substrate holder 64 in the X-axis and Y-axis directions. The film formation unit 60 also includes an injection nozzle 66 having a slit 67 formed at its tip for injecting the aerosol onto the single crystal SiC layer 20, and a vacuum pump 68 that reduces the pressure in the film formation chamber 62. The injection nozzle 66 is attached to the tip of the raw material supply pipe 54.
[0032] It is known that the AD method may cause pores in the film or the film may become a powder compact depending on the film formation conditions. For example, it is easily affected by the collision speed of the raw material powder with the substrate, the particle size of the raw material powder, the agglomeration state of the raw material powder in the aerosol, the amount sprayed per unit time, etc. The collision speed of the raw material powder with the substrate is affected by the pressure difference between the film formation chamber 62 and the spray nozzle 66, the opening area of the spray nozzle, etc. Therefore, in order to obtain a dense polycrystalline SiC layer, it is necessary to appropriately control these factors.
[0033] In the thermal CVD method, a known film forming apparatus such as a commercially available one can be used. The source gas is not particularly limited, but silicon tetrachloride (SiCl4) gas or silane (SiH4) gas can be used as a Si source, and methane (CH4) gas or propane (C3H8) gas can be used as a C source. The film forming temperature is preferably 1000 to 2200°C, more preferably 1100 to 2000°C, and even more preferably 1200 to 1900°C.
[0034] It is known that the formation of a polycrystalline SiC layer on a single-crystalline SiC layer using thermal CVD is affected by the deposition temperature, the gas flow rates of the Si source and the C source and their ratio, the deposition pressure, etc. The deposition temperature has a large effect, and a lower deposition temperature is preferable, preferably less than 1700°C, more preferably 1500°C or less, and even more preferably 1400°C or less. However, if the deposition temperature is too low, the deposition rate itself will also decrease, so from the viewpoint of the deposition rate, a higher deposition temperature is preferable.
[0035] In the case of a method in which a SiC compact is placed on a single crystal SiC layer, the polycrystalline SiC layer can be produced by molding the raw material powder. For example, when press molding is used, the polycrystalline SiC layer is a press molded body. The press molded body can be produced by press molding the raw material powder of the polycrystalline SiC layer based on a known method, for example, by placing the raw material powder in a mold and pressing it at a pressure of preferably 100 to 400 kgf / cm. 2 , more preferably 150 to 300 kgf / cm 2The molding method is not particularly limited, and in addition to press molding, tape molding, extrusion molding, casting molding, doctor blade method, and any combination thereof can be used. For example, when tape molding is used, it is preferable to add additives such as binders, plasticizers, dispersants, and dispersion media to the raw material powder to make a slurry, and then pass the slurry through a thin slit-shaped discharge port to discharge and mold it into a sheet. There is no limitation on the thickness of the molded body molded into a sheet, but from the viewpoint of handling, it is preferable that it is 5 to 500 μm. In addition, if a thick polycrystalline SiC layer is required, a large number of these sheet molded bodies can be stacked and used to obtain the desired thickness. In addition, the SiC molded body may be in a sintered state, and in this case, the molded body may contain additives such as sintering aids in addition to the SiC raw material. EXAMPLES
[0036] The present invention will now be further illustrated by the following examples.
[0037] Example 1 (1) Preparation of polycrystalline SiC layer As the raw material powder for the AD film formation, a commercially available fine β-SiC powder (volume basis D50: 0.7 μm) was prepared. In addition, a commercially available substrate with a diameter of about 50 mm (2 inches) was prepared, in which a 3C-SiC film (single crystal SiC layer) was epitaxially grown to 3.5 μm on a 900 μm thick Si single crystal substrate. The raw material powder was sprayed onto the 3C-SiC surface of the substrate using the AD device 50 shown in FIG. 1 to form an AD film.
[0038] The AD film formation conditions were as follows. First, the carrier gas was N2, and a ceramic nozzle with a slit of 7 mm long side x 0.6 mm short side was used for film formation. The nozzle scan conditions were a scan speed of 0.6 mm / s, and the nozzle was moved 56 mm in a direction perpendicular to the long side of the slit and forward, 7 mm in the direction of the long side of the slit, 56 mm in a direction perpendicular to the long side of the slit and returning, and 7 mm in the direction of the long side of the slit and in the opposite direction to the initial position, and when the nozzle moved 56 mm from the initial position in the direction of the long side of the slit, the nozzle was scanned in the opposite direction to the direction up to that point, and the cycle of returning to the initial position was counted as one cycle, and this cycle was repeated 1200 times. In one cycle of film formation at room temperature, the set pressure of the carrier gas was adjusted to 0.04 MPa, the flow rate to 9 L / min, and the pressure in the chamber to 100 Pa or less. The thickness of the AD film formed in this way was about 300 μm. In this way, a polycrystalline SiC layer (AD film) was formed on the surface of the 3C-SiC film formed on the Si single crystal substrate.
[0039] (2) Polishing the polycrystalline SiC layer The substrate with the AD film formed was removed from the AD device, and the polycrystalline SiC layer was ground to #6000 using a grindstone to make the surface flat. The surface was then smoothed by lapping using diamond abrasive grains. The size of the abrasive grains was gradually reduced from 3 μm to 0.5 μm to improve flatness. After that, a mirror finish was performed using chemical mechanical polishing (CMP) using colloidal silica.
[0040] (3) Removal of the Si substrate Next, the surface of the Si substrate was ground to #6000 using a grindstone to make the surface flat. The surface was then smoothed by lapping using diamond abrasive grains. The size of the abrasive grains was gradually reduced from 3 μm to 0.5 μm to improve flatness. Then, a mirror finish was performed using chemical mechanical polishing (CMP) using colloidal silica, and finally the Si substrate was completely removed. In this way, a SiC composite substrate was obtained, which had a 2.0 μm thick 3C-SiC film (single crystal SiC layer) and a polycrystalline SiC layer with a thickness of about 300 μm.
[0041] (4) Evaluation of polycrystalline SiC layer (4-1) Surface FE-EPMA Using an electron probe microanalyzer (FE-EPMA) (manufactured by JEOL Ltd., JXA-8500F), the composition analysis of the surface of the polycrystalline SiC layer of the obtained SiC composite substrate was carried out with a probe size of 30 μm × 30 μm. Also, this measurement was carried out at 10 locations on the surface of the polycrystalline SiC layer. The conditions for this FE-EPMA measurement were as follows.
[0042] <FE-EPMA measurement conditions> · Acceleration voltage: 15 kV · Irradiation current: 50 nA
[0043] As a result of the surface FE-EPMA measurement, rare earth elements were not detected on the surface of the polycrystalline SiC layer, and Si, C, and O were detected. Using the quantified values of the detected Si and C, the weight ratio of the content of rare earth elements in the polycrystalline SiC layer to the total content of rare earth elements, Si, and C (rare earth elements / (rare earth elements + Si + C)) was determined. The value of the content of each element is the average value of the values obtained from the above 10 measurements. The results are shown in Table 1.
[0044] (5) Formation of GaN film A GaN film was formed on the 3C-SiC film of the SiC composite substrate fabricated as described above by the MOCVD method. In the growth of the GaN film, TMG (trimethylgallium) was used as the Ga source gas, NH3 (ammonia) was used as the N source gas, and nitrogen and hydrogen were used as the carrier gases. The film formation temperature was 1100 °C and the film formation time was 1 hour. The thickness of the obtained GaN film was approximately 1.0 μm.
[0045] (6) Evaluation of GaN film (6-1) Crystallinity of GaN film XRC measurement of the (002) plane of the GaN film formed on the SiC composite substrate was carried out using an XRD device (D8-DISCOVER, manufactured by Bruker-AXS). In practice, 2θ, ω, χ, and φ were adjusted to set the axis so that the peak of the (002) plane of GaN appeared, and then the following conditions were used: tube voltage 40 kV, tube current 40 mA, anti-scattering slit 3 mm, ω = 14.0 to 22.0° range, ω step width 0.005°, and counting time 0.5 seconds. In addition, the X-ray source used was a Ge (022) asymmetric reflection monochromator that converted CuKα rays into parallel monochromatic light. The half-width of the XRC profile of the (002) plane of the obtained GaN film was determined by smoothing the profile using XRD analysis software (LEPTOS Ver. 4.03, manufactured by Bruker-AXS) and then searching for a peak. The results obtained were rated according to the following evaluation criteria and are shown in Table 1.
[0046] - Grade A: Half-width is 400 arcsec or less - Grade B: Half-width is more than 400 arcsec. and less than 500 arcsec. - Grade C: Half-width exceeds 500 arcsec.
[0047] As a result of evaluation of the crystallinity of the GaN film, the half-width of the (002) plane XRC profile was 400 arcsec or less, indicating good crystallinity.
[0048] (6-2) Number of cracks in GaN film Using an industrial microscope (Nikon, ECLIPSE, LV150N), the eyepiece was set to 10x and the objective lens to 5x, and the entire surface of the GaN film was observed in polarized and differential interference modes. If cracks were observed, the objective lens was changed to 10x and an image was taken. Only cracks with a length of 50 μm or more were counted as cracks. In addition, if the distance between one crack and another was 500 μm or less, it was considered to be one crack. Regardless of the size of the GaN film, the number of cracks (pieces) on the entire surface of the film was counted, and the number of cracks was counted for a film area of 20 cm. 2 The results were converted into the number of cracks per unit. Table 1 shows the results.
[0049] Example 2 In the above (3), a SiC composite substrate was prepared, a GaN film was formed, and various evaluations were performed in the same manner as in Example 1, except that when removing the Si substrate, the thickness of the 3C-SiC film was set to 1.1 μm. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, no rare earth elements were detected, but Si, C, and O were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 500 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0050] Example 3 In the above (3), a SiC composite substrate was fabricated, a GaN film was formed, and various evaluations were performed in the same manner as in Example 1, except that when removing the Si substrate, the thickness of the 3C-SiC film was set to 3.0 μm. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, no rare earth elements were detected, but Si, C, and O were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0051] Example 4 (comparison) In the above (3), a SiC composite substrate was prepared, a GaN film was formed, and various evaluations were performed in the same manner as in Example 1, except that the thickness of the 3C-SiC film was set to 0.9 μm when removing the Si substrate. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, no rare earth elements were detected, but Si, C, and O were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film exceeded 500 arcsec, and the crystallinity was poorer than that of Example 1. Because the crystallinity was poor, the number of cracks was not evaluated. The results are shown in Table 1.
[0052] Example 5 In the above (1), as raw material powder for AD film formation, commercially available fine β-SiC powder (volume basis D50: 0.7 μm) containing 96.0 wt % and yttrium oxide powder (volume basis D50: 0.1 μm) containing 4.0 wt % were prepared, and mixed in ethanol for 24 hours using SiC balls in a ball mill, and dried to obtain a mixed powder. Except for this, the SiC composite substrate was produced, the GaN film was formed, and various evaluations were performed in the same manner as in Example 1. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, Si, C, O, and Y as a rare earth element were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0053] Example 6 In the above (1), as raw material powder for AD film formation, commercially available fine β-SiC powder (volume standard D50: 0.7 μm) containing 99.98 wt % and yttrium oxide powder (volume standard D50: 0.1 μm) containing 0.02 wt % were prepared, and mixed in ethanol for 24 hours using SiC balls and dried to obtain a mixed powder. Except for this, the SiC composite substrate was produced, the GaN film was formed, and various evaluations were performed in the same manner as in Example 1. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, Si, C, O, and Y as a rare earth element were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0054] Example 7 In the above (1), as raw material powder for AD film formation, commercially available fine β-SiC powder (volume standard D50: 0.7 μm) containing 99.97 wt % and yttrium oxide powder (volume standard D50: 0.1 μm) containing 0.03 wt % were prepared, and mixed in ethanol for 24 hours using SiC balls and dried to obtain a mixed powder. Except for this, the SiC composite substrate was produced, the GaN film was formed, and various evaluations were performed in the same manner as in Example 1. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, Si, C, O, and Y as a rare earth element were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0055] Example 8 In the above (1), as raw material powder for AD film formation, commercially available fine β-SiC powder (volume basis D50: 0.7 μm) containing 88.0 wt% and yttrium oxide powder (volume basis D50: 0.1 μm) containing 12.0 wt% were prepared, and mixed in ethanol for 24 hours using SiC balls in a ball mill, and dried to obtain a mixed powder. Except for this, the SiC composite substrate was produced, the GaN film was formed, and various evaluations were performed in the same manner as in Example 1. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, Si, C, O, and Y as a rare earth element were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0056] Example 9 In the above (1), as raw material powder for AD film formation, commercially available fine β-SiC powder (volume basis D50: 0.7 μm) containing 76.0 wt% and yttrium oxide powder (volume basis D50: 0.1 μm) containing 24.0 wt% were prepared, and mixed in ethanol for 24 hours using SiC balls in a ball mill, and dried to obtain a mixed powder. Except for this, the SiC composite substrate was produced, the GaN film was formed, and various evaluations were performed in the same manner as in Example 1. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, Si, C, O, and Y as a rare earth element were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0057] Example 10 In the above (1), 70.0 wt% of commercially available fine β-SiC powder (volume standard D50: 0.7 μm) and 30.0 wt% of yttrium oxide powder (volume standard D50: 0.1 μm) were prepared as raw powder for AD film formation, and mixed in a ball mill using SiC balls in ethanol for 24 hours and dried to obtain a mixed powder. Except for this, the SiC composite substrate was produced, the GaN film was formed, and various evaluations were performed in the same manner as in Example 1. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, Si, C, O, and Y were detected as a rare earth element. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0058] Example 11 In the above (1), as raw material powder for AD film formation, commercially available fine β-SiC powder (volume standard D50: 0.7 μm) containing 96.0 wt % and samarium oxide powder (volume standard D50: 0.1 μm) containing 4.0 wt % were prepared, and mixed in ethanol for 24 hours using SiC balls in a ball mill, and dried to obtain a mixed powder. Except for this, the SiC composite substrate was produced, the GaN film was formed, and various evaluations were performed in the same manner as in Example 1. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, Si, C, O, and Sm as a rare earth element were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0059] Example 12 In the above (1), as raw material powder for AD film formation, commercially available fine β-SiC powder (volume basis D50: 0.7 μm) containing 96.0 wt% and yttrium oxide powder (volume basis D50: 0.1 μm) containing 4.0 wt% were prepared, and mixed in ethanol for 24 hours using SiC balls in a ball mill, and then dried to obtain a mixed powder. Other than this, (1) the preparation of a polycrystalline SiC layer, (2) the polishing of the polycrystalline SiC layer, and (3) the removal of the Si substrate were performed in the same manner as in Example 1. In this way, a SiC composite substrate was obtained that had a 2.0 μm-thick 3C-SiC film (single crystal SiC layer) and a polycrystalline SiC layer with a thickness of about 300 μm.
[0060] After that, a 3C-SiC film was further formed on the 3C-SiC film of the SiC composite substrate by the CVD method. In growing the 3C-SiC film, trichlorosilane and ethylene were used as the source gas, and hydrogen was used as the carrier gas. The film formation temperature was 1380°C, and the 3C-SiC film was formed until it reached a thickness of 40 μm.
[0061] Next, the 3C-SiC film was ground to #6000 using a grindstone to flatten the plate surface. The plate surface was then smoothed by lapping using diamond abrasive grains. The size of the abrasive grains was gradually reduced from 3 μm to 0.5 μm to improve flatness. After that, a mirror finish was performed using chemical mechanical polishing (CMP) using colloidal silica, and finally a SiC composite substrate was obtained with a 30 μm-thick 3C-SiC film (single crystal SiC layer) and a polycrystalline SiC layer with a thickness of approximately 300 μm.
[0062] The SiC composite substrate thus obtained was subjected to the formation of a GaN film and various evaluations in the same manner as in Example 1. As a result of FE-EPMA measurement of the surface of the polycrystalline SiC layer, Si, C, O and Y as a rare earth element were detected. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1.
[0063] Example 13 (comparison) A commercially available substrate with a diameter of approximately 50 mm (2 inches) was prepared, in which 3C-SiC (single crystal SiC layer) was epitaxially grown to a thickness of 3.0 μm on a 900 μm thick Si single crystal substrate. A GaN film was formed on the 3C-SiC film of this substrate by MOCVD. In growing the GaN film, TMG (trimethylgallium) was used as the Ga source gas, NH3 (ammonia) as the N source gas, and nitrogen and hydrogen were used as the carrier gas. The film formation temperature was 1100°C, and the film formation time was 1 hour. The thickness of the obtained GaN film was approximately 1.0 μm.
[0064] The GaN film thus obtained was evaluated in the same manner as in Example 1. When the crystallinity of the GaN film was evaluated, the half-width of the (002) plane XRC profile of the GaN film was 400 arcsec or less, indicating good crystallinity. The results are shown in Table 1. As described above, in Example 13, a polycrystalline SiC layer was not formed, and the GaN film was formed on a composite substrate in which 3C-SiC (single crystal SiC layer) was formed on a Si single crystal substrate, so the polycrystalline SiC layer was not evaluated.
[0065]
Table 1
Claims
1. A SiC composite substrate comprising a polycrystalline SiC layer and a single-crystal SiC layer having a thickness of 1.0 to 30 μm on the polycrystalline SiC layer, the polycrystalline SiC layer further containing a rare earth element.
2. The SiC composite substrate according to claim 1, wherein the single crystal SiC layer has a thickness of 2.0 to 30 μm.
3. The SiC composite substrate according to claim 1 or 2, wherein the polycrystalline SiC layer has a thickness of 100 to 5000 μm.
4. The SiC composite substrate according to any one of claims 1 to 3, wherein the polytype of the single crystal SiC layer is 3C.
5. The SiC composite substrate according to any one of claims 1 to 4, wherein the rare earth element is Y and / or Sm.
6. The SiC composite substrate according to any one of claims 1 to 5, wherein the rare earth element is Y.
7. The SiC composite substrate according to any one of claims 1 to 6, wherein the weight ratio of the content of the rare earth element to the total content of the rare earth element, Si and C in the polycrystalline SiC layer is 0.00020 to 0.20.
Citation Information
Patent Citations
Combustion controlling apparatus of internal combustion engine
JP1979033909A
Actuator controller
JP1988087375A
PRODUCTION OF SiC COMPOSITE SUBSTRATE
JP2017057102A
Single crystal sic and its manufacturing method
JP3254557B2